Poly (ADP-Ribose) and α-synuclein extracellular vesicles in patients with Parkinson disease: A possible biomarker of disease severity. - Fabrice Lucien; Eduardo E Benarroch; Aidan Mullan; Farwa Ali; Bradley F Boeve; Michelle M Mielke; Ronald C Petersen; Yohan Kim; Cole Stang; Emanuele Camerucci; Owen A Ross; Zbigniew K Wszolek; et al. (PLoS ONE, 2022)
Background/objective Despite multiple attempts, no surrogate biomarker of Parkinson disease (PD) has been definitively identified. Alternatively, identifying a non-invasive biomarker is crucial to understanding the natural history, severity, and progression of PD and to guide future therapeutic trials. Recent work highlighted alpha synuclein-containing extracellular vesicles and Poly (ADP-ribose) polymerase (PARP-1) activity as drivers of PD pathogenesis and putative PD biomarkers. This exploratory study evaluated the role of alpha-synuclein-positive extracellular vesicles and PARP-1 activity in the plasma of PD patients as non-invasive markers of the disease's severity and progression. Methods We collected plasma of 57 PD patients (discovery cohort 20, replication cohort 37) and compared it with 20 unaffected individuals, 20 individuals with clinically diagnosed Alzheimer's disease, and 20 individuals with dementia with Lewy bodies. We analyzed alpha-synuclein-positive extracellular vesicles from platelet-free plasma by nanoscale flow cytometry and blood concentrations of poly ADP-ribose using sandwich ELISA kits. Results Median concentration of α-synuclein extracellular vesicles was significantly higher in PD patients compared to the other groups (Kruskal-Wallis, p < .0001). In the discovery cohort, patients with higher α-synuclein extracellular vesicles had a higher Unified Parkinson Disease Rating Scale score (UPDRS III median = 22 vs. 5, p = 0.045). Seven out of 20 patients (35%) showed detectable PAR levels, with positive patients showing significantly higher levels of α-synuclein extracellular vesicles. In the replication cohort, we did not observe a significant difference in the PAR-positive cases in relationship with UPDRS III. Conclusions Non-invasive determination of α-synuclein-positive extracellular vesicles may provide a potential non-invasive marker of PD disease severity, and longitudinal studies are needed to evaluate the role of α-synuclein-positive extracellular vesicles as a marker of disease progression.